Extracellular Vesicle-Mediated Delivery of Ultrasmall Superparamagnetic Iron Oxide Nanoparticles to Mice Brain - Kutchy, Naseer A.; Ma, Rong; Liu, Yutong; Buch, Shilpa; Hu, Guoku (Frontiers in Pharmacology, 2022)
Extracellular vesicles (EVs) are small lipid membrane-bound vesicles that can pass the blood-brain barrier. Therefore, EVs could be used for the delivery of therapeutics into the brain. Herein, we investigated the biodistribution of intranasal perfusion of ultrasmall superparamagnetic iron oxide (USPIO) labeled astrocyte-derived EVs (ADEVs) in mice. We used western blotting, transmission electron microscopy (TEM), Nanoparticle uptake assay to characterize ADEVs.In addition, intranasal perfusion coupled with magnetic resonance imaging (MRI) was employed to determine the distribution of USPIO labeled ADEVs in mice. Our results showed the uptake of USPIO by mouse astrocytes as well as ADEVs. In addition, we confirmed the biodistribution of ADEVs in the brain, and other internal organs, including the kidney, liver, and spleen. Our results suggest that USPIO did not affect mouse astrocyte cell survivability and EV release. Therefore, intranasal delivery of therapeutic loaded EVs could be used for the treatment of various brain disorders.